The Implementation of Roleplay Method to Improve Learning Outcomes in the Topic of Applying Healthy Living - Khasanah, Novika Imamatul; Dinata, Vega Candra; Arifin, Zainal (JOURNAL RESPECS (Research Physical Education and Sports), 2024)
Applying engaging learning methods has a positive effect on the understanding and comprehension of students. When instructional materials are delivered in an interesting way, students tend to actively engage in the learning process, especially for learners aged 6-7 years. Role play is an effective learning approach for children. By implementing this method with children, teachers or parents can create engaging, interactive, and effective learning experiences. This method plays a crucial role in helping children develop various skills and essential understanding during their developmental stage. The aim of this study is to determine the learning outcomes using the role play method. This research utilizes the Classroom Action Research (CAR) method. The research instruments consist of observation and worksheets. The research results indicate an improvement in student learning outcomes: a 25% increase in the "low" category during the pre-action phase, 50% in the "low" category during cycle I, and 90% in the "excellent" category during cycle II.